Establishing a green biodesulfurization process for iron ore concentrates in stirred tank and leaching column bioreactors using Acidithiobacillus thiooxidans - Bobadilla-Fazzini, Roberto A.; Poblete-Castro, Ignacio (Frontiers in Bioengineering and Biotechnology, 2023)
The presence of sulfur impurities in complex iron ores represents a significant challenge for the iron mining and steel-making industries as their removal often necessitates the use of hazardous chemicals and energy-intensive processes. Here, we examined the microbial and mineralogical composition of both primary and secondary iron concentrates, identifying the presence of Sulfobacillus spp. and Leptospirillum spp., while sulfur-oxidizing bacteria were absent. We also observed that these concentrates displayed up to 85% exposed pyrrhotite. These observations led us to explore the capacity of Acidithiobacillus thiooxidans to remove pyrrhotite-sulfur impurities from iron concentrates. Employing stirred tank bioreactors operating at 30 °C and inoculated with 5•10 6 (At. thiooxidans cells mL -1 ), we achieved 45.6% sulfur removal over 16 days. Then, we evaluated packed leaching columns operated at 30 ºC, where the At. thiooxidans enriched system reached 43.5% desulfurization over 60 days. Remarkably, sulfur removal increased to 80% within 21 days under potassium limitation. We then compared the At. thiooxidans-mediated desulfurization process, with and without air supply, under potassium limitation, varying the initial biomass concentration in 1-meter columns. Aerated systems facilitated approximately 70% sulfur removal across the entire column with minimal iron loss. In contrast, non-aerated leaching columns achieved desulfurization levels of only 6% and 26% in the lower and middle sections of the column, respectively. Collectively, we have developed an efficient, scalable biological sulfurremoval technology for processing complex iron ores, aligning with the burgeoning demand for sustainable practices in the mining industry.